A comparison of the distribution of stroke and footwork type in top-level men`s vs. women`s table tennis - Malagoli Lanzoni, I.; Di Michele, R.; Merni, F. (World Congress of Performance Analysis of Sport IX, 2012)
Technical and tactical skills play a crucial role as determinants of performance in table tennis. A method well-recognized as effective for technical and tactical evaluation in racket sports is notational analysis (Hughes, 1998), in which relevant aspects of the actions performed by the players during play are collected and summarized using specific indicators. The most used technical and tactical indicators in net games are descriptors of shot characteristics, such as the distribution of shot types and of shot outcomes (Hughes & Bartlett, 2002). Another important characteristic of a shot is the footwork performed before the hit, as using a proper footwork allows the player to be in the most favorable position to hit the ball effectively (Malagoli Lanzoni et al., 2007). The purpose of this study was to compare top-level men`s and women`s matches with respect to the distribution of footwork and stroke types used by the players. Ten men`s (M) and five women`s (W) matches were selected in which both the opponents were in the top 30 of the male/female world ranking. Video recordings were analyzed in slow motion with the software Kinovea by an operator who, while watching the match, recorded on a spreadsheet the footwork technique and the stroke type used for each shot. Chi-square tests showed significant differences (p< 0.001) between M and W in the distribution of both footworks and strokes. The percentage of serves was slightly higher in M (19.4 %) than W (16.0 %), indicating a lower number of shots per rally in M. The push, used in most cases to counter the serve, represented 15.8 % and 13.0 % of total strokes in M and W, respectively. The top spin was the most frequent stroke type in both M (25.4%) and W (28.8%). A relevant difference between M and W concerned the strokes used to continue the rally after the initial exchanges. In fact, male players adopted more often the "top spin counter top spin" stroke type (M: 15.4 % vs. W: 7.4 %), reflecting their preference for a counterattacking strategy. Conversely, female players used mostly passive and defensive strokes as the block (20.9% vs. M: 13.9%), and the drive (10.1 % vs. M: 0.1%). The "one step" footwork was the most frequent in M (31.9% vs. W:19.8 %), followed by the chassè (24.0 % vs. W: 19.3 %). The pivot, associated to attacking shots, was more frequent in M (13.1 %) than W (7.9 %), similarly to the crossover (M: 9.7%, W: 3.8%). In the majority of cases, female players hit the ball without performing any footwork (43.5% vs. M: 18.2%). In conclusion, male players showed a more aggressive style of play than female players, with a wider use of offensive strokes and footworks.